1996
DOI: 10.1002/(sici)1097-0215(19960301)65:5<700::aid-ijc23>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of cytokines against opportunistic vascular tumors in mice

Abstract: o 1996 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…17 In particular, anti -H5V hemangiosarcoma responses were found to be potentiated by IFN and IL -12, while they were abrogated by anti -T-cell antibodies. 17,19,39 Our analysis of H5V lesions expression profiles indicated that inhibition of disease development in infected mice was associated with the persistent infiltration of stagnating tumors with activated effectors (CTL and NK ) cells. Thus, we hypothesize that the parvovirus -mediated toxicity of NS1 for H5V cells stimulated intrinsic immune reaction, and that this response was intensified when the virus expressed IP -10 transgene in addition to its own NS1 and NS2 genes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…17 In particular, anti -H5V hemangiosarcoma responses were found to be potentiated by IFN and IL -12, while they were abrogated by anti -T-cell antibodies. 17,19,39 Our analysis of H5V lesions expression profiles indicated that inhibition of disease development in infected mice was associated with the persistent infiltration of stagnating tumors with activated effectors (CTL and NK ) cells. Thus, we hypothesize that the parvovirus -mediated toxicity of NS1 for H5V cells stimulated intrinsic immune reaction, and that this response was intensified when the virus expressed IP -10 transgene in addition to its own NS1 and NS2 genes.…”
Section: Discussionmentioning
confidence: 86%
“…(c ) Although no total cure was achieved, responding to therapy mice stayed alive for more than 6 months, which represents an over 100 days increase in their life expectancy ( the equivalent of 10 years of human lifespan ). The antitumor protection provided by MVMp / IP -10 is quite impressive because H5V model is an especially aggressive case of experimental hemangiosarcomas, which are usually refractory to complete cure by various treatments, 16,39,44,45 with IL-12 therapy being the most successful one. 19 The antineoplastic activity of IP -10 is not without precedents, although the use of different delivery systems and tumor models precludes published data from being quantitatively compared with the present ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes suggest a possible relationship between the dierent levels of PymT and of pp60 c-src activity and the dierences in the proliferative response of EC. In contrast, murine EC lines carrying mT and established by embryonic tissues have an increased and permanent activation of signaling pathways triggered by mT, including phosphatidylinositol 3-kinase (Dong et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Altematively, IL-12 may inhibit tumour cell proliferation by triggering IFN-y production by T lymphocytes and NK cells Nastala et al, 1994). Our previous studies indicated that IFN-y suppresses H5V cell proliferation in vitro as well as tumour growth in vivo (Dong et al, 1996). In line with these findings, we observed that anti-IFN-y MAb co-administration abrogated the anti-tumour effect conferred by IL-12 treatment, thus IFN-y production is essential for anti-tumour activity of IL-12.…”
Section: Discussionmentioning
confidence: 99%